La nobiltà di Seggio napoletana e il riuso politico dell'Antico tra Quattro e Cinquecento: Il "Libro terczo de regimento de l'Opera de li homini jllustri sopra de le medaglie" di Pietro Jacopo de Jennaro The Neapolitan Seggio Nobility and the Reception of Classical Antiquity between the Fifteenth and Sixteenth Centuries: The "Libro terczo de regimento de l'Opera de li hominj illustri sopra de le medaglie" of Pietro Jacopo de Jennaro - Monica Santangelo (Regna: Testi e studi su istituzioni, cultura e memoria del Mezzogiorno medievale, 2019)
[English]:The specific attention paid to the Florentine «civic humanism» and the success of "republican" paradigm achieved by the Anglo-American historiography are responsible, in various forms, for limiting differently historical interests in the princely and monarchical contexts of the late Middle Ages Italian peninsula. This tendency, joined with the serious documentary loss of the Naples State Archive, put so far the Seggi élites of many Southern mainland cities away on the margins of historical international debate.During the 15th century the reception of the Antiquity transformed the legitimacy languages and the power practices both of the princes and of the whole peninsula urban élites. Which auctores did they inspire to? Which is the relationship between the classicism and the institutional reform proposals? This book tries to answer to these questions, focusing on the Naples context, not deeply investigated, through the study and the critical edition of Pietro Jacopo de Jennaro's Libro terczo de regimento de l'Opera de le medaglie. It is a book wrote between 1500 and 1504, as free comment in form of medaglie to Livy's Ab urbe condita libri, in order to legitimize the political prominence of Seggi antiqui lineages and to propose a new mixed government. By studying this work it is possible to identify the debates developed during the Aragonese kingdom fall, concerning the relationships between representation and obedience, consensus and legitimacy, and to offer new ways to rethink the humanistic political classicism and the establishments of oligarchical urban governments between the 15th and 16th centuries.[Italiano]: La particolare attenzione riservata all'«umanesimo civile» fiorentino e l'affermarsi nella storiografia anglo-americana del paradigma "repubblicano" hanno contribuito, in forme diverse, a limitare l'interesse degli storici per i contesti principeschi e monarchici della penisola italiana nel tardo Medioevo. Questa tendenza, unita alle gravi perdite documentarie dell'Archivio di Stato di Napoli, ha relegato finora le élites ascritte ai Seggi di numerose città del Regnum ai margini del dibattito storiografico internazionale. Nel corso del Quattrocento il riuso dell'Antico non trasformò solo i linguaggi di legittimità e l'azione dei principi, ma anche quelli delle élites urbane dell'intera penisola. A quali auctores essi s'ispirarono? Qual è il rapporto tra il classicismo e i progetti di riforme istituzionali? Il volume prova a rispondere a tali quesiti, soffermandosi sul contesto napoletano, finora poco indagato, attraverso l'analisi e l'edizione critica del Libro terczo de regimento de l'Opera de le medaglie di Pietro Jacopo de Jennaro. Si tratta di un'opera composta tra il 1500 e il 1504, come libero commento in medaglie agli Ab urbe condita libri di Livio, per ridefinire la preminenza politica della più antica nobiltà dei Seggi e per proporre un nuovo modello di governo misto. Attraverso l'esame di tale opera si ripercorrono i dibattiti relativi al rapporto tra rappresentanza e obbedienza, tra consenso e legittimità negli ultimi anni del regno dei Trastámara, offrendo nuovi spunti per ripensare il classicismo politico umanistico e i processi di chiusura oligarchica tra Quattro e Cinquecento.